Disseminated Intravascular Coagulation and Malignancy: A Case Report and Literature Review - Sohal, Sumit (Case Rep Oncol Med, 2020)
Disseminated Intravascular Coagulation (DIC) is a disorder of coagulation which is commonly seen as a complication of infections, traumas, obstetric diseases, and cancers especially hematological and rarely solid cancers. DIC may rarely be the presenting feature of an undiagnosed malignancy. It may present in the form of different phenotypes which makes its diagnosis difficult and leads to high mortality. The treatment comprises supportive, symptomatic treatment and removal of the underlying source. Here, we present a patient with history of being on warfarin for atrial fibrillation and other comorbidities who presented with elevated INR of 6.3 and increasing dyspnea on exertion. Over the course of her stay, her platelet counts started dropping with a concurrent decrease in fibrinogen levels. She eventually developed pulmonary embolism, followed by stroke and limb ischemia, which was indicative of the thrombotic phenotype of DIC. Her pleural fluid analysis showed huge burden of malignant cells in glandular pattern suggestive of adenocarcinoma and was started on heparin drip. However, the patient had cardiac arrest and expired on the same day of diagnosis.